The Potential of Religious Radicalism Movement in Banyumas - Widyaningsih, Rindha; Sumiyem, S; Kuntarto, K (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
Religious radicalism is the trigger for the occurrence of terrorism which is an extraordinary crime and an enemy of all the countries that exist in the world. Since Indonesia as a country has a high vulnerability to religious radicalism, it is important to conduct studies on religious radicalism both nationally and regionally. Knowing the level and potential of religious radicalism is a step for the creation of a comprehensive mechanism of prevention and treatment of religious radicalism. The position of Banyumas as an inter-provincial gateway becomes very strategic for radical groups to spread their ideology and mindset. The ease of inter-regional access underpinned by good supporting facilities and infrastructure is an important point of consideration for radical groups to spread their ideas. Interviews were conducted to obtain data from stakeholders who handle radicalism. the findings were elaborated with supporting literature to provide a more comprehensive result. The results of this study indicate that Banyumas has great potential for the growth and development of religious radicalism, and Banyumas people have high vulnerability to get exposed and influenced by the idea of radicalism caused by factors of religious behavior, geography, culture, technology and information development, and demography. However, so far the level of religious radicalism in Banyumas is still low because there is good cooperation between the stakeholders and the community. Radikalisme agama merupakan pemicu bagi terjadinya terorisme yang merupakan kejahatan luar biasa dan menjadi musuh semua negara yang ada di dunia. Indonesia sebagai negara yang memiliki kerawanan yang tinggi terhadap radikalisme agama penting untuk melakukan kajian-kajian mengenai radikalisme agama baik dalam tingkat nasional maupun regional. Mengetahui tingkat dan potensi radikalisme agama merupakan langkah bagi terciptanya mekanisme pencegahan dan penanganan radikalisme agama yang komprehensif. Posisi Banyumas sebagai pintu gerbang antar provinsi menjadi sangat strategis bagi kelompok-kelompok radikal untuk menyebarkan ideologi dan pola pikirnya. Kemudahan akses antar wilayah yang ditopang dengan kondisi sarana dan prasarana pendukung wilayah yang baik menjadi poin penting pertimbangan bagi kelompok radikal untuk menyebarkan pahamnya. Wawancara dilakukan untuk mendapatkan data dari stakeholder yang menangani radikalisme. Hasil temuan lalu dielabrasi dengan literatur pendukung untuk memberikan gambaran yang lebih komprehensif. Hasil penelitian ini menunjukkan bahwa Banyumas memiliki potensi besar bagi tumbuh dan berkembangnya radikalisme agama, dan masyarakat Banyumas memiliki kerentanan yang tinggi terpapar dan terpengaruh paham radikalisme yang disebabkan karena faktor perilaku beragama, faktor geografis, faktor kultural, faktor perkembangan teknologi dan informasi, serta faktor demografi. Namun demikian sejauh ini tingkat radikalisme agama di Banyumas masih termasuk rendah. Hal tersebut karena adanya kerjasama penanggulangan yang baik antara stakeholder dan masyarakat.